PIK3CA-related overgrowth with an uncommon phenotype: case report - Roberta Rotunno; Andrea Diociaiuti; Elisa Pisaneschi; Claudia Carnevale; Marialisa Dentici; May El Hachem (BMC, 2022)
Abstract Background Megalencephaly-capillary malformation syndrome is a rare multiple-malformation syndrome secondary to somatic activating mutations in the PI3K-AKT-MTOR pathway. This is included in a heterogeneous group of disorders, now defined "PIK3CA-related overgrowth spectrum". Case presentation We report a 22-months-old female presenting an uncommon phenotype associated with a genetic mosaicism in the PIK3CA gene, detected on DNA extracted from blood peripheral and tissue biopsy. Conclusions NGS is the preferred method for molecular diagnosis of PROS on affected skin and overgrown tissues as primary samples. The wide phenotypic variability is based on the distribution of mosaicism, in fact the same mutation can cause different PIK3CA related disorders. Continuous understanding of the clinical spectrum and of molecular basis of PROS and their overlap will lead to improve diagnosis, management and new treatment strategies.